2016
DOI: 10.15389/agrobiology.2016.6.883eng
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Gastrointestinal Microbiome Changes During Ontogenesis

Abstract: A b s t r a c tMicroorganisms which inhabit gut play great role in providing with nutrients, antibiotics, hormones and vitamins necessary for poultry health and performance. Therefore study of gut microbiome changes during ontogenesis seems to be essential. The structure of gut microflora in poultry embryos is of particular interest and debated because of very few publications on the problem. Despite embryo intestine is commonly considered sterile there are several reports on gut colonization by microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The examination of microbiocenosis in the caecum at 23 dpi revealed an additional colonisation of intestinal contents by Peptococcus and Staphylococcus representatives. Our data was consistent with the results obtained in other studies (e.g., Li et al [125]; Fisinin et al [126]; Lu et al [127]; Józefiak et al [128]; Singh et al [129]). For example, Li et al [125], based on the 16S rRNA gene sequencing, showed that microbial communities of the chicken intestine were dominated by Firmicutes and Proteobacteria (>90%), the former being represented by Peptostreptococcaceae , Lachnospiraceae , Ruminococcaceae , and the genus Enterococcus .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The examination of microbiocenosis in the caecum at 23 dpi revealed an additional colonisation of intestinal contents by Peptococcus and Staphylococcus representatives. Our data was consistent with the results obtained in other studies (e.g., Li et al [125]; Fisinin et al [126]; Lu et al [127]; Józefiak et al [128]; Singh et al [129]). For example, Li et al [125], based on the 16S rRNA gene sequencing, showed that microbial communities of the chicken intestine were dominated by Firmicutes and Proteobacteria (>90%), the former being represented by Peptostreptococcaceae , Lachnospiraceae , Ruminococcaceae , and the genus Enterococcus .…”
Section: Discussionsupporting
confidence: 94%
“…Our study demonstrated that the caecal microbiota in growing chickens tended to be more diverse by 23 dpi, especially in Subgroups II and IV. Similar observations of an elevation in bacterial diversity were also made by Fisinin et al [126] for healthy chick embryos and 26-day-old chicks when exploring changes in the bacterial community in the digestive tract in chicken ontogenesis.…”
Section: Discussionsupporting
confidence: 83%
“…For gut microbiota analysis from chickens at 17 wk of age, 8 samples of GI contents were taken from caecums in the intestine and then the composition was determined by Terminal Restriction Fragment Length Polymorphism [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intestines of farm animals and poultry play an important role not only in the assimilation of nutrients from feed but also in maintaining the immune defense of the organism ( Grozina, 2014 ; Fisinin et al, 2016 ). The barrier function of intestinal villi (microvillus cylindrical epithelium) cannot completely protect the organism from the introduction of pathogenic bacteria and viruses without populating with a variety of beneficial microflora.…”
Section: Introductionmentioning
confidence: 99%